2019
DOI: 10.3389/fpsyt.2019.00228
|View full text |Cite
|
Sign up to set email alerts
|

Use of Gabapentin in the Treatment of Substance Use and Psychiatric Disorders: A Systematic Review

Abstract: Objective: Gabapentin (GBP) is an anticonvulsant medication that is also used to treat restless legs syndrome (RLS) and posttherapeutic neuralgia. GBP is commonly prescribed off-label for psychiatric disorders despite the lack of strong evidence. However, there is growing evidence that GBP may be effective and clinically beneficial in both psychiatric disorders and substance use disorders. This review aimed to perform a systematic analysis of peer-reviewed published literature on the efficacy of GBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 87 publications
0
49
0
Order By: Relevance
“…Suffice it to say that the literature supports a well-established efficacy of gabapentinoids for traditional neuropathic pain indications, with numerous systematic reviews and meta-analyses demonstrating significant and superior benefit in these states [7,8]. Gabapentinoids also demonstrate extra-analgesic utility, including anxiolysis [9], amelioration of restless legs syndrome [10], slow-wave sleep enhancement [11], and substance use disorder mitigation [12,13].…”
Section: The Therapeutic Benefits Of Gabapentinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suffice it to say that the literature supports a well-established efficacy of gabapentinoids for traditional neuropathic pain indications, with numerous systematic reviews and meta-analyses demonstrating significant and superior benefit in these states [7,8]. Gabapentinoids also demonstrate extra-analgesic utility, including anxiolysis [9], amelioration of restless legs syndrome [10], slow-wave sleep enhancement [11], and substance use disorder mitigation [12,13].…”
Section: The Therapeutic Benefits Of Gabapentinoidsmentioning
confidence: 99%
“…Gabapentinoids have been frequently used (off-label) in addiction medicine settings for facilitating detoxification/managing withdrawal symptoms, as well as for chronic conditions, i.e., relapse-prevention efforts, for numerous drugs of abuse, including opioids, cannabis, and alcohol, the latter of which represents the arena of most study [12,13,58]. These (and other anticonvulsants) carry substantial advantage over the tradition-rich benzodiazepines in terms of increased safety/no interactions with alcohol, but also in terms of no evident cross-substance dependence and transfer of addiction [35,57].…”
Section: Mechanism: (Translational) Addiction Behavior Analysismentioning
confidence: 99%
“…As a reference, Gabapentin has been used for treating other substance-related problems, for instance, alcohol-related problems (Ahmed et al, 2019;Berlin et al, 2015;Howland, 2013;Howland, 2014;Soyka & Mutschler, 2016). At least some benefit has been reported for treating cravings (Ahmed et al, 2019;Berlin et al, 2015), withdrawal symptoms (Ahmed et al, 2019;Berlin et al, 2015;Howland, 2013), and alcohol dependence (Howland, 2013;Howland, 2014;Soyka & Mutschler, 2016). However, Gabapentin has not shown benefit for treating cocaine dependence (Ahmed et al, 2019;Howland, 2013;Minozzi et al, 2015) or tobacco dependence (Sood et al, 2010).…”
Section: Gabapentin Use In Researchmentioning
confidence: 99%
“…At least some benefit has been reported for treating cravings (Ahmed et al, 2019;Berlin et al, 2015), withdrawal symptoms (Ahmed et al, 2019;Berlin et al, 2015;Howland, 2013), and alcohol dependence (Howland, 2013;Howland, 2014;Soyka & Mutschler, 2016). However, Gabapentin has not shown benefit for treating cocaine dependence (Ahmed et al, 2019;Howland, 2013;Minozzi et al, 2015) or tobacco dependence (Sood et al, 2010).…”
Section: Gabapentin Use In Researchmentioning
confidence: 99%
“…However, naltrexone has not been shown to be universally efficacious alone, which may be due to the associated symptoms experienced during the phases of early abstinence, incorporating both insomnia, as well as mood instability [13]. Conversely, literature suggests the efficacy of gabapentin in the management of AUD, with abilities to provide both the reduction of these symptoms and the prevention of early relapse [3,5,13]. Recent clinical trials have indicated a longer interval to heavy drinking during the first six weeks of the abstinence period with patients taking naltrexone combined with gabapentin [13].…”
Section: Off-label Use Of Gabapentin In the Treatment Of Audmentioning
confidence: 99%